2000
DOI: 10.1084/jem.192.4.557
|View full text |Cite
|
Sign up to set email alerts
|

Naive T Cells Transiently Acquire a Memory-like Phenotype during Homeostasis-Driven Proliferation

Abstract: In a depleted lymphoid compartment, naive T cells begin a slow proliferation that is independent of cognate antigen yet requires recognition of major histocompatibility complex–bound self-peptides. We have followed the phenotypic and functional changes that occur when naive CD8+ T cells undergo this type of expansion in a lymphopenic environment. Naive T cells undergoing homeostasis-driven proliferation convert to a phenotypic and functional state similar to that of memory T cells, yet distinct from antigen-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

52
504
4
7

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 590 publications
(567 citation statements)
references
References 43 publications
(74 reference statements)
52
504
4
7
Order By: Relevance
“…It has long been observed that transfer of small numbers of T cells into lymphopenic hosts results in T-cell expansion, a process described as homeostatic proliferation [9][10][11][12][13][14][15][16]. As the T cells proliferate, they assume an Ag-experienced or memory phenotype, which is indicated by upregulation of CD44, Ly6C and CD122 (IL-2-IL-15Rβ) [12,15].…”
Section: A Link Between Lymphodepletion and Augmented Immune Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been observed that transfer of small numbers of T cells into lymphopenic hosts results in T-cell expansion, a process described as homeostatic proliferation [9][10][11][12][13][14][15][16]. As the T cells proliferate, they assume an Ag-experienced or memory phenotype, which is indicated by upregulation of CD44, Ly6C and CD122 (IL-2-IL-15Rβ) [12,15].…”
Section: A Link Between Lymphodepletion and Augmented Immune Functionmentioning
confidence: 99%
“…As the T cells proliferate, they assume an Ag-experienced or memory phenotype, which is indicated by upregulation of CD44, Ly6C and CD122 (IL-2-IL-15Rβ) [12,15]. This T-cell expansion and acquisition of a memory phenotype is also associated with enhanced effector functions, determined by ex vivo analysis of interferon-γ (IFN-γ) release and cytolysis [12,14,15]. In a recent autoimmunity study, King et al showed that the inherent lymphopenia in non-obese diabetic (NOD) mice and increased expression of IL-21 drives the homeostatic expansion of autoreactive cells, precipitating self-tissue destruction [17].…”
Section: A Link Between Lymphodepletion and Augmented Immune Functionmentioning
confidence: 99%
“…46 Homeostatic proliferation in response to lymphopenia is driven by TCR interaction with peptide-MHC on APCs and cytokines, such as IL-7 and IL-15. 47 We found that the alloreactive CD8 T cell response in draining pLNs was associated with a significant conversion of naïve to memory type cells (central memory and effector memory) and increased proliferation in both CD8 T cell replete (only responding to bm1 antigens at day 13 post-Tx) and CD8 T cell depleted mice (responding to bm1 antigens and to lymphopenia at day 21 post-Tx).…”
Section: Discussionmentioning
confidence: 99%
“…46 These T cells repopulating the peripheral compartment precipitate allograft rejection and resist protocols for tolerance induction. 51 Our data calls for precaution in solid organ transplantation under tolerogenic protocols involving extensive depletion of lymphocytes or leukocytes with agents such as ATG or alemtuzumab (anti-CD52 mAb) with partial depleting properties over NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that during homeostasisdriven proliferation, naive T cells acquire a memory-like or activated phenotype characterized by increased expression of the surface markers CD44 and Ly6-c, but not down-regulated CD62L expression, which differs from "true" antigen-experienced memory/effector T cells [7][8][9][10][11]. Consistently, we found that it was the irradiation and reconstitution manipulation rather than vaccination that increased the percentage of CD44 hi CD62L hi cells (from 34.8% to 50.8% in unvaccinated mice and from 34.8% to 44.7% in vaccinated mice) and CD8 + Ly6-c + cells (data not shown).…”
Section: Vaccinated Rlm Have a High Percentage Of Memory/effector T Cmentioning
confidence: 99%